The apoptotic and genomic studies on A549 cell line induced by silver nitrate - Ayse Kaplan; Gulsen Akalin Ciftci; Hatice Mehtap Kutlu (Tumor Biology)
Lung cancer is the leading cause of male cancer deaths worldwide. Metal-based anticancer drugs have evolved significantly during the past decades. Recently, silver ions have been investigated for their anticancer effects. We aimed to study the time-course cytotoxic effects of silver nitrate on A549 adenocarcinomic human alveolar basal epithelial cells to provide insights into the molecular-level understanding of growth suppression mechanism involved in apoptosis. The influences of silver nitrate were studied via MTT assay, flow cytometry, immunocytochemical, confocal and transmission electron microscopy, and microarray assays. Silver nitrate showed inhibitory effects against A549 cells in a dose- and time-dependent manner for 24, 48, and 72 h and induced apoptosis. The early and late apoptotic cells and depolarized mitochondrial membrane potential were determined by the half-maximal inhibitory concentration (IC 50 ) value of silver nitrate treated for 72 h. But cysteinyl aspartate proteinase-3 was not activated for 72 h. Furthermore, IC 50 value of silver nitrate also induced apoptosis according to immunocytochemical assays for 72 h. The downregulated CCNY , HNRNPL , ASF1B , PIAS4 , HNRNPH1 , EIF2C2 , TAF15 , FOXC1 , LEP , and PCB2 genes administered with silver nitrate IC 50 were identified as apoptosis-leading genes. Silver nitrate may be a suitable therapeutic agent against lung cancer.